Effect of Surface Treatments on the Bond Strength between Composite Resin and Acrylic Resin Denture Teeth - Vergani, Carlos Eduardo [UNESP]; Machado, Ana Lucia [UNESP]; Giampaolo, Eunice Teresinha [UNESP]; Pavarina, Ana Claudia [UNESP] (My University, 2000)
Purpose: This investigation studied the effects of 3 surface treatments on the shear bond strength of a light-activated composite resin bonded to acrylic resin denture teeth. Materials and Methods: The occlusal surfaces of 30 acrylic resin denture teeth were ground flat with up to 400-grit silicon carbide paper. Three different surface treatments were evaluated: (1) the flat ground surfaces were primed with methyl methacrylate (MMA) monomer for 180 seconds; (2) light-cured adhesive resin was applied and light polymerized according to the manufacturer's instructions; and (3) treatment 1 followed by treatment 2. The composite resin was packed on the prepared surfaces using a split mold. The interface between tooth and composite was loaded at a cross-head speed of 0.5 mm/min until failure. Results: Analysis of variance indicated significant differences between the surface treatments. Results of mean comparisons using Tukey's test showed that significantly higher shear bond strengths were developed by bonding composite resin to the surfaces that were previously treated with MMA and then with the bonding agent when compared to the other treatments. Conclusion: Combined surface treatment of MMA monomer followed by application of light-cured adhesive resin provided the highest shear bond strength between composite resin and acrylic resin denture teeth.
Keywords: acrylic acid resin; adhesive agent; methacrylic acid methyl ester; resin cement; wetting agent; analysis of variance; dental bonding; materials testing; nonparametric test; randomization; tensile strength; tooth prosthesis; Acrylic Resins; Adhesives; Analysis of Variance; Composite Resins; Dental Bonding; Materials Testing; Methylmethacrylate; Random Allocation; Resin Cements; Statistics, Nonparametric; Tensile Strength; Tooth, Artificial; Wetting Agents